2011
DOI: 10.1016/j.jmb.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A Crystallographic Study of the Role of Sequence Context in Thymine Glycol Bypass by a Replicative DNA Polymerase Serendipitously Sheds Light on the Exonuclease Complex

Abstract: Thymine glycol (Tg) is the most common oxidation product of thymine and is known to be a strong block for replicative DNA polymerases. A previously solved structure of the bacteriophage RB69 DNA polymerase (RB69 gp43) in complex with Tg in the sequence context 5’-G-Tg-G shed light on how Tg blocks primer elongation: The protruding methyl group of the oxidized thymine displaces the adjacent 5’-G which can no longer serve as a template for primer elongation. [Aller, P., Rould, M.A., Hogg, M, Wallace, S.S., & Dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
1
27
1
Order By: Relevance
“…A local conformational perturbation may also be at play here. The presence of (5R,6S)-Tg within double-stranded DNA is known to hinder proper stacking of the 5Ј base, especially when that base is a purine (45,59,60). Furthermore, the nature of the base opposite the lesion was shown to modulate repair of Tg by human NEIL1 (49); Tg occupies the wobble position when mispaired with G (61) and is excised much more rapidly than Tg:A (49).…”
Section: Discussionmentioning
confidence: 99%
“…A local conformational perturbation may also be at play here. The presence of (5R,6S)-Tg within double-stranded DNA is known to hinder proper stacking of the 5Ј base, especially when that base is a purine (45,59,60). Furthermore, the nature of the base opposite the lesion was shown to modulate repair of Tg by human NEIL1 (49); Tg occupies the wobble position when mispaired with G (61) and is excised much more rapidly than Tg:A (49).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DNA replication accessory proteins, particularly the sliding clamp gp45, may be involved in the process of translocating DNA from polymerase to exonuclease active site [15]. It has also been shown that a β hairpin loop between residues 251–262 is important for exonuclease function [48,49]. This loop is involved in stabilizing the frayed base pair at the exonuclease active site allowing the removal of the incorrect nucleotide.…”
Section: Catalytic Cycle Of B Type Polymerase Rb69gp43mentioning
confidence: 99%
“…The three unpaired bases of the primer strand are then sequestered into the exonuclease active site, which facilitates the excision. Structures of RB69gp43 poised with its primer-template in the exonuclease mode are available [47,48]. …”
Section: Catalytic Cycle Of B Type Polymerase Rb69gp43mentioning
confidence: 99%
“…an "up" or "down" conformation as seen in the recent structure of RB69 phage DNA polymerase. 20 The tip of this particular motif does not contain the Y255-G256 motif of T4 PolB (Y257-G258 for RB69 PolB) that has been shown to be required for DNA replication fidelity. 21 Nevertheless, the β-hairpin loop and arginine 265 block the P/T junction from two different sides (Fig.…”
Section: Structures Of Pabpolb In Editing Modementioning
confidence: 99%